1997
DOI: 10.3171/foc.1997.3.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical reconstruction of the musculocutaneous nerve in traumatic brachial plexus injuries

Abstract: Over the last 16 years, 345 surgical reconstructions of the brachial plexus were performed using nerve grafting or neurotization techniques in the Neurosurgical Department at the Nordstadt Hospital, Hannover, Germany. Sixty-five patients underwent graft placement between the C-5 and C-6 root and the musculocutaneous nerve to restore the flexion of the arm. A retrospective study was conducted, including statistical evaluation of the following pre- and intraoperative parameters in 54 patients: 1) time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…We have also previously reported an inverse relationship between graft length and functional recovery. 38 In the present study, shorter grafts (Ͻ 12 cm) have shown a positive impact on the restoration of elbow flexion in nerve transfer from the accessory nerve to the musculocutaneous nerve, compared with longer grafts (Ͼ 12 cm). Patients treated with nerve grafts shorter than 12 cm showed a significantly higher reinnervation rate compared with patients treated with grafts longer than 12 cm.…”
Section: Length Of the Nerve Graftsmentioning
confidence: 77%
See 2 more Smart Citations
“…We have also previously reported an inverse relationship between graft length and functional recovery. 38 In the present study, shorter grafts (Ͻ 12 cm) have shown a positive impact on the restoration of elbow flexion in nerve transfer from the accessory nerve to the musculocutaneous nerve, compared with longer grafts (Ͼ 12 cm). Patients treated with nerve grafts shorter than 12 cm showed a significantly higher reinnervation rate compared with patients treated with grafts longer than 12 cm.…”
Section: Length Of the Nerve Graftsmentioning
confidence: 77%
“…38 In the current study, a significantly better outcome in elbow flexion after nerve transfer with the accessory nerve occurred in patients treated during the first 6 months after brachial plexus injury.…”
Section: Time Interval Between Trauma and Surgerymentioning
confidence: 87%
See 1 more Smart Citation
“…6,7 Poor outcome from clinical peripheral nerve injury is especially evident when repair is performed in a delayed fashion. 22,25,[43][44][45]47,48 This has been variously attributed to the lengthy periods of chronic axotomy (defined as the period during which injured neurons remain without target connections) and of chronic denervation of distal Schwann cells and target organs. These conditions independently and collectively progressively reduce regenerative capacity, as we have previously documented and reviewed.…”
mentioning
confidence: 99%
“…
OR treatment of brachial plexus injury with nerve root avulsion a number of nerves have been used for neurotization, 12,15,17 including the intercostal, accessory, 9 and the hypoglossal nerves, 8 the contralateral brachial plexus nerve roots, 5 and the motor branches of the cervical plexus. 20 The sheer number of different treatment options clearly indicates that there is no ideal one.
…”
mentioning
confidence: 99%